2006
DOI: 10.1152/ajplung.00167.2005
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical stretch-induced serotonin release from pulmonary neuroendocrine cells: implications for lung development

Abstract: (serotonin, and peptides (e.g., bombesin, calcitonin) with growth factor-like properties and are thought to play an important role in lung development. Because physical forces are essential for lung growth and development, we investigated the effects of mechanical strain on 5-HT release in PNEC freshly isolated from rabbit fetal lung and in the PNEC-related tumor H727 cell line. Cultures exposed to sinusoidal cyclic stretch showed a significant 5-HT release inhibitable with gadolinium chloride (10 nM), a block… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(64 citation statements)
references
References 36 publications
1
60
0
3
Order By: Relevance
“…3,4,17,18 Tph1 is expressed in lung pulmonary neuroendocrine cells, and both hypoxia and mechanical stretch have been shown to induce increased Tph1 expression and serotonin release in rabbit lung. 19 In light of these observations, our results suggest that, in mice, chronic hypoxia itself may induce Tph1 synthesis and subsequent serotonin release, which acts as a mitogen in pulmonary arteries, contributing to the pulmonary vascular remodeling and subsequent onset of pulmonary hypertension. The elevation of pulmonary vascular tone that accompanies PAH is likely to induce further stretch-induced Tph1 expression and serotonin release.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…3,4,17,18 Tph1 is expressed in lung pulmonary neuroendocrine cells, and both hypoxia and mechanical stretch have been shown to induce increased Tph1 expression and serotonin release in rabbit lung. 19 In light of these observations, our results suggest that, in mice, chronic hypoxia itself may induce Tph1 synthesis and subsequent serotonin release, which acts as a mitogen in pulmonary arteries, contributing to the pulmonary vascular remodeling and subsequent onset of pulmonary hypertension. The elevation of pulmonary vascular tone that accompanies PAH is likely to induce further stretch-induced Tph1 expression and serotonin release.…”
Section: Discussionmentioning
confidence: 58%
“…Hypoxia and mechanical stretch have been shown increase Tph1 expression and serotonin release in rabbit lung. 19 Hence, hypoxia may induce Tph1, which results in an elevation of peripheral serotonin, which contributes to hypoxia-induced PAH. The resulting increased pulmonary pressure and vessel tension may then lead to further Tph1 expression and serotonin release.…”
Section: Perspectivesmentioning
confidence: 99%
“…Serotonin and other peptides (eg, bombesin, calcitonin) with growth factor-like properties are thought to play an important role in normal lung development. 18 PNECs are most noticeably present in the perinatal period, particularly in species that are relatively immature at birth such as humans and, in addition to their role in lung development, may have a crucial contribution in adaptation to air breathing at birth. 19 NEBs are considered to serve as airway chemoreceptor cells responsive to hypoxia and are thought to activate vagal afferents, thereby participating in the regulation of breathing.…”
Section: Neuroendocrine System Of the Lungmentioning
confidence: 99%
“…Alveolar type II cells also have a tryptophan hydroxylase activity that suggests their ability to produce 5-HT from the amino acid, tryptophan (40). Recent publications have shown that 5-HT can be released in the respiratory system by the neuroendocrine epithelial cells after exposure to hypoxia or epithelial stretch (10,11), two common conditions found in patients with ALI. Hypoxia is known to cause an inhibition of ion transport across the distal lung epithelium (4).…”
Section: Discussionmentioning
confidence: 99%
“…Its role in the pathophysiology of asthma and pulmonary hypertension is well established (7)(8)(9). The lung neuroendocrine system, represented by pulmonary neuroepithelial cells in upper airway and neuroepithelial bodies in distal airway (including alveoli), is able to secrete 5-HT into the airspace under various stimuli, such as hypoxia and epithelial stretch (10,11), two conditions commonly observed in patients with ALI. Therefore, under these conditions, locally secreted 5-HT could modulate the function of epithelial ion channels, including ENaC, and affect its function.…”
mentioning
confidence: 99%